Energy Security for Poland – Autonomous or Complementary Categories? Consequences for Public Policy - Dobroczyńska, Agnieszka; Juchniewicz, Leszek (Journal of Public Governance, 2009)
This article is definitely not devoted to assessing the status of energy security. Rather, the authors took a different approach to it, showing how ways of thinking about the state and about governing determine what character is assumed by the category of energy security, and its role in the economy. The contention of the authors is that the practice of governing principally entails relatively separate treatment of the particular aims of the energy economy, with no account being taken of crucial conditions and interdependences, in particular the sensitivity of the economy to energy eo ipso energy security. The authors go on to consider that immediate actions, and sometimes even the freedom and at the same time changeability of priorities in line with the cycle provided by the political dominance calendar reflect the lack of a systematic framework in line with which to shape economic policy and its components, including energy policy. Inadequate education of politicians (in particular a lack of knowledge of economics) and a lack of imaginations (alternative thinking ability) are also important factors. The authors introduce examples form conceptual approaches to energy policy, suggesting directions to take in order to change the blameworthy practice of recent years and to make an effective start with using the interdependences of the country’s development strategy. Reference is also made to certain methodological and procedural circumstances that could help guarantee harmonious alignments of the complementary aims of energy policy.